2014
DOI: 10.7557/3.2607
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite assessment of walrus (<i>Odobenus rosmarus rosmarus</i>) stocks in Canada

Abstract: Walruses (Odobenus rosmarus rosmarus) occur in Canada from James Bay to Smith Sound and from the Canada-Greenland international boundary in Davis Strait to the longitudinal center of Canada (Fig. 1). Within this range, walruses are subdivided into seven stocks based on summering areas for the purpose of making management decisions that affect walrus and walrus habitat (Stewart 2008). Stock assessments (e.g. Breiwik and York 2009, Lugten 2010) rely on identifying units that can be managed without impact on othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 38 publications
(69 reference statements)
3
25
0
Order By: Relevance
“…The levels of genetic variation were similar to those observed in walruses (0.53-0.61, Shafer et al 2014) and other pinnipeds (HE = 0.59 to 0.81; Palo et al 2001, Hoelzel et al 2001, Davis et al 2002, Acevedo-Whitehouse et al 2003 elsewhere. They are also consistent with results in Andersen et al (2009), which included a subsample of the animals in this study (HE = ranging from 0.59-0.66) that had been examined with fewer markers.…”
Section: Genetic Variationsupporting
confidence: 80%
“…The levels of genetic variation were similar to those observed in walruses (0.53-0.61, Shafer et al 2014) and other pinnipeds (HE = 0.59 to 0.81; Palo et al 2001, Hoelzel et al 2001, Davis et al 2002, Acevedo-Whitehouse et al 2003 elsewhere. They are also consistent with results in Andersen et al (2009), which included a subsample of the animals in this study (HE = ranging from 0.59-0.66) that had been examined with fewer markers.…”
Section: Genetic Variationsupporting
confidence: 80%
“…Recent work using microsatellites showed that walruses in central Canada are subdivided into two large subpopulations – known as the high and central Arctic – that might be attributed to vicariance during the last glacial maximum (Shafer et al . ). Further, dispersal seems to be predominantly from the north to the south (Shafer et al .…”
Section: Introductionmentioning
confidence: 97%
“…Further, dispersal seems to be predominantly from the north to the south (Shafer et al . ) and the species showed no clear genetic signature of a bottleneck (Andersen et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…When walrus were seen, we revised the coordinates for the haulout site as required. Shafer et al 2014). Stock designations as used here (Stewart 2008) In 2005, aerial surveys were conducted using a Messerschmitt-Bolkow-Blohm (BO-105-CBS) helicopter based on the Canadian Coast Guard (CCG) icebreaker Henry Larsen.…”
Section: Methodsmentioning
confidence: 99%
“…1), two of which are shared with Greenland (Born et al 1995, NAMMCO 2006, Stewart 2008, Andersen et al 2009, Dietz et al 2014). The Hudson Bay-Davis Strait (HB-DS) stock, part of the central-Arctic population of walrus in Canada (Shafer et al 2014) ranges from West Greenland to eastern Baffin Island and into Hudson Strait, although it is thought the occupancy range in this region has diminished in modern history (COSEWIC 2006). Walrus in this stock are hunted in both Canada and Greenland (Born et al 1995, Priest andUsher 2004) but there is only limited information on the size of the population that supports these harvests.…”
Section: Introductionmentioning
confidence: 99%